2016
DOI: 10.12659/msm.901861
|View full text |Cite
|
Sign up to set email alerts
|

Reference Intervals of Alpha-Fetoprotein and Carcinoembryonic Antigen in the Apparently Healthy Population

Abstract: BackgroundThe aim of this study was to calculate 95% reference intervals and double-sided limits of serum alpha-fetoprotein (AFP) and carcinoembryonic antigen (CEA) according to the CLSI EP28-A3 guideline.Material/MethodsSerum AFP and CEA values were measured in samples from 26 000 healthy subjects in the Shuyang area receiving general health checkups. The 95% reference intervals and upper limits were calculated by using MedCalc.ResultsWe provided continuous reference intervals from 20 years old to 90 years ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…In our study, we compared two widely used automated CEA assays. 80% of healthy subjects have CEA concentration <3 ng/mL (13). In Architect CMIA and Cobas ECLIA based on the Levey-Jennings quality control test report, was <2 SD.…”
Section: Discussionmentioning
confidence: 92%
“…In our study, we compared two widely used automated CEA assays. 80% of healthy subjects have CEA concentration <3 ng/mL (13). In Architect CMIA and Cobas ECLIA based on the Levey-Jennings quality control test report, was <2 SD.…”
Section: Discussionmentioning
confidence: 92%
“…In a previous research, Qin et al reported an upper limit of 4.76 IU/ml for AFP in male individuals residing in a defined area in China (21). Zhang et al reported an upper limit of 7.51 IU/ml for AFP (22). The authors have attributed varying upper limits to the different methodologies used in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Reference interval in tumour markers reference intervals (upper limit) for Zhuang ethnic males was 5.12 ng/mL for CEA (30). Zhang et al reported an upper limit of 4.53ng/ml for CEA (22). Researchers show that the reference interval is changed by gender, smoking, ethnicity and different detection systems.…”
Section: Discussionmentioning
confidence: 99%
“…The Ethics Committee of Shuyang People's Hospital approved this study. Reference samples were chosen according to CLSI CA28‐A3 guideline and a previous report …”
Section: Methodsmentioning
confidence: 99%